Improving Precise Orbit Determination of LEO Satellites Using Enhanced Solar Radiation Pressure Modeling - Youcun Wang; Min Li; Kecai Jiang; Wenwen Li; Qile Zhao; Rongxin Fang; Na Wei; Renhai Mu (Space Weather)
Abstract Precise orbit knowledge is a fundamental requirement for low Earth orbit (LEO) satellites. High‐precision non‐gravitational force modeling directly improves the overall quality of LEO precise orbit determination (POD). To address the potential systematic errors in solar radiation pressure (SRP), we introduce observed radiation data and modeled physical effects to describe the real in‐flight environment of satellites. Time‐dependent solar irradiance data and a highly physical shadow model are considered for SRP modeling. We develop an advanced thermal reradiation model for satellite solar panels. A set of improved non‐gravitational force models is performed for LEO POD, and we discuss the benefits of the enhanced dynamic models on orbit quality and dependence on empirical parameters. The Gravity Recovery and Climate Experiment Follow‐On (GRACE‐FO), Jason‐3, and Haiyang‐2B missions are selected for the POD process. Estimated empirical acceleration and scale parameters and independent satellite laser ranging (SLR) are used to validate the final orbit solutions. The magnitude of empirical acceleration estimated in POD is reduced by 19% with the enhanced dynamic modeling, and the estimated scale factor for the SRP converges to stable and reasonable level. Furthermore, the steady‐state temperature model used in thermal reradiation can effectively reduce mismodeled effects in the SRP, and the systematic linear dependency revealed by the SLR residuals is significantly reduced for the GRACE‐C and Jason‐3 satellites, with improvements of approximately 61% and 49%, respectively. Overall, advances are made in the explicit modeling of non‐gravitational forces to pursue superior satellite orbits, suggesting a more dynamic orbit solution.